Pengaruh Promosi Dalam Mempengaruhi Pembelian Tanpa Perencanaan (Impulse Buying) Pada Suzuya Medan - Mervin Angeline (Sekolah Tinggi Manajemen Bisnis (STMB) MultiSmart, 2017)
This research is conducted to analyze the influence of sales promotion on impulse buying at Suzuya Market Medan. The Goal of this research is also to know the sales promotion that influence the impulse buying , supporting factors and how the problems take place. This research use The descriptive-verificative method.. Field study covers observation, interview and structural questionnaires. The questionnaires are given to 45 consumers at Suzuya Medan. Data collection methods are literature and field studies The sistematic sampling is used as sampling tecgnique. Data are analyzed by qualitative analysis and correlation regresion statistical. The analysis confirms that there are influences on sales promotion, impulse buying at Hypermarket Bandung. That is, if sales promotion is carefully done, it will increase the impulse buying.